Robe's restricted three-body problem with drag - Giordano, Claudia Marcela (1997)
Robe's restricted three-body problem is investigated with regards to the effects of a linear drag force. In particular. the stability of the model's equilibrium points is studied in this respect. Two scenarios are envisaged: the one originally discussed by Robe himself and the one suggested by him and recently analyzed by the present authors, that assumes for the fluid body the structure of a Roche's ellipsoid.